Customary Land Rights in Positive Law (Agrarian Law) and Islamic Law in Indonesia - Falahy, Lutfi El; Giyarsi, Giyarsi; Birahmat, Budi (Jurnal Kawakib, 2024)
Abstract This study examines the intersection of customary land rights (hak ulayat) and Islamic inheritance law within Indonesia's positive legal framework. Customary land rights, deeply embedded in the social fabric of indigenous communities, represent collective ownership and stewardship that have been integral to Indonesia's agrarian system. These rights are formally recognized in the 1945 Constitution and the Basic Agrarian Law of 1960, reflecting the nation's cultural heritage and communal values. The integration of adat law and Islamic law highlights the adaptability of these legal systems, particularly through concepts such as musha' (collective ownership) and ihya’ al-mawat (revitalizing unused land), which align with the principles of maqasid shariah to ensure justice, public welfare, and sustainability. Despite their alignment, the implementation of these principles faces challenges, including regulatory complexities and conflicts between national development goals and indigenous claims. This paper employs a qualitative, descriptive-analytical approach to explore how communal land rights and inheritance practices are recognized and adapted within Islamic and national legal frameworks. It underscores the potential for harmonizing customary law with modern legal structures to promote equitable resource management, protect indigenous rights, and achieve sustainable development. The findings emphasize the critical role of maqasid shariah in reconciling traditional practices with contemporary governance, offering insights into fostering legal and social integration in Indonesia.